PROBLEMATIKA MENULIS BAHASA ARAB - Putri, Neli (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
Writing is one of language skills that should be acquired by Arabic students. It may be difficult for students to learn Arabic because it is one foreign languages. Many students get difficulties in writing in Arabic language because they should pay attention to imlaiyah structure in writing words to sentences. It is very danger If the students write a verse of Alquran and hadist incorrectly. Indeed, the understanding of structure of Arabic in writing should be taken in to account as importance skill by Arabic and Islamic education students.